Chinese Environmental Ethics and Whitehead's Philosophy - Wang, Zhihe (Environmental ethics, 2020)
Environmental ethics is a major topic of discussion and enactment in China. The government is committed to work toward an "ecological civilization," a society in which concerns for a healthy natural environment are interwoven with concerns for a healthy human society and healthy human relations with nature. Whereas in the United States concern for the environment is rarely consciously philosophical, Chinese history has made people aware that philosophy underlies and shapes public policy. Whitehead's thought has been welcomed as a way of clarifying and supporting the commitment to ecological civilization, which has been strongly reemphasized by President Xi. It also helps in reviving and incorporating classical Chinese thought without threatening the great advances China has made in science. This organic thinking has expressed itself in government policy in shifting from the industrialization of agriculture to support for eco-villages and in dethroning GDP as the measure of progress. The interest in Whitehead is expressed by thirty-six universities setting up Centers for Process Studies, extensive discussion of a process book - Organic Marxism - and numerous other publications.